India’s Science, Technology and Innovation Policy: Choices for Course Correction with Lessons Learned from China - G.D. Sandhya (STI Policy and Management Journal, 2018)
A large number of developed and emerging economies have introduced S&T reforms and some of them such as Japan, South Korea and later China have used them for gaining competitive advantage in science, technology and innovation through well crafted S&T policies and appropriate strategies. So far, India has pronounced four major S&T policies beginning with the Science Policy Resolution (SPR) in 1958, Technology Policy in 1983; S&T Policy in 2003 and Science Technology and Innovation Policy in 2013. In a period of six decades India has created a huge S&T infrastructure and made impressive achievements in space, defence and atomic energy, yet the feat is not as impressive in the industrial sector. In innovation competitiveness, R&D and human resource, the indices related to global manufacturing, competition, innovation and knowledge, India has not performed as well in comparison to other BRICS countries. In this paper an attempt has been made to look at, how comprehensive India’s STI policies with regard to policy components; a roadmap; strategies for execution and boldness in terms of identifying and recognising the failures and recommend major structural changes. What is intended is to understand the relationship between the domain of S&T policy and intended outcomes; the mismatch between the policy expectations and outcomes. An attempt is being made to identify possibility for correction  by taking lessons from other economies, such as China. Keywords:   S&T policies, Innovation policies, Innovation ecosystem